Institutions of Jewish Basic Education in the Abbasid Period: Beth Hassephers And Beth Hamidrashs - (:unkn) unknown (TURK TARIH KURUMU, 2014)
Living in excile for centuries had taught the Jewish people that the only way for them to survive as a community was through education. Because of this, the establishment of primary and secondary educationial institutions in every organized community was a vital issue. Religious leaders often emphasized education was one of the most important religious duties and encouraged their communities to educate their children. The costs for children of poor households and orphans were covered by the community leaders. The basis of Jewish education in the Abbasid period constituted of the teaching of the Torah and the Talmud. Children entered primary school, which was known as the beth hassepher, at the age of 6 or 7. Alongside the Torah education, they were taught as much Hebrew as was needed for daily prayers and they were also instructed in basic worshipping rituals. Another goal of the primary schools was to instruct the children in proper Jewish norms and conduct. In paralel with the integration into the Islamic society children were also taught basic arithmetic and Arabic script. Jewish secondary education was given at the beth hamidrash, which is known as bayt al-midras in Islamic sources. The beth din was responsible for the management of the bay al-midras, which were built next to the synagogues. The education at the bay al-midras, which was more disciplined compared to the primary schools, was focused on the Mishna and the Talmud. The Jews were one of the most organized communities in terms of educational institutions during the Abbasid Period. Whose organizational experience based on first centuries CE, Jews understood well that education was vital in making Messianic community before Mesiah would come. So, they gave up riots in vain and struggled for educating the Jewish community religious education. This situation set them apart from the society which they lived in, enabled them to keep existance as a community throughout the history as well. Jews, who gave priority to religious education disregarding the conditions, still continue to hold this behavior. They educate their children in the community schools which they established both in Israel and in other spots on the world.
Keywords: Abbasids; Jews; Jewish history; Jewish Education; Jewish Elementary School; Beth Hassepher; Jewish Adult Education; Beth Hamidrash; History of Education